Канюк звичайний (Buteo buteo) в Миколаївській області - Редінов, К.О. (Бранта: Cборник научных трудов Азово-Черноморской орнитологической станции, 2009)
Данные собраны на двух стационарах, а также во время экспедиций в 1991-2008 гг. В Николаевской области сельхозугодья занимают 86% суши, лесистость – 7 %. Первые гнездовые находки канюка (Buteo buteo vulpinus) известны с конца 1930-х гг. в искусственных лесо-насаждениях. До 1970-х гг. канюк был редким на гнездовании. В 1980-х гг. отмечены увеличение численности вида и начало заселения им агроценозов. В последующие годы вид стремительно расселялся. На стационарах плотность гнездования вида составляет 0.43-0.5 пар на 10 км². Современная численность канюка оценена в 500 пар. The data have been collected on two fixed plots, as well as during expeditions in 1991-2008. In Mykolaiv region agricultural fields cover 86% of the land, forested area - 7%. The first nesting finds of the Common Buzzard (Buteo buteo vulpinus) are known since the late 1930s. in planted forests. Until the 1970s the Buzzard was rare on breeding. In the 1980s the species numbers increased and it began occupying agrocenoses. In subsequent years, the species rapidly settled the area. On fixed plots the density of species breeding is 0.43-0.5 pairs per 10 km². The current Buzzard population is estimated at 500 pairs.